R code for a latent class analysis of the UK Biobank data - Yapp, Emma; Davis, Katrina; Coleman, Jonathan; Booth, Tom (King's College London, 2020)
(PLEASE NOTE: a newer version of this dataset (Version 2) is available. Please see the Links section for the link to access it.)R code to conduct a sex-stratified latent class analysis of trauma in the UK Biobank Mental Health Questionnaire cohort. Associations of resultant classes and recent/current mental health are explored using regressions. Associations of socio-demographic variables with class membership are additionally reported.
Keywords: Latent class analysis; R; Mental health; Violence; Women’s mental health